Covalently interconnected layers in g-C3N4: toward high mechanical stability, catalytic efficiency and sustainability - Roy, Raj Sekhar; Mondal, Sanjit; Mishra, Samita; Banoo, Maqsuma; Sahoo, Lipipuspa; Kumar, Amit; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Applied Catalysis B: Environmental, 2023)
The grim prospects for the industrial utilization of g-C3N4 nanosheets arise from multi-step processing resulting in low material yields and poor visible light response due to quantum confinement. Herein, we introduce a strategy for linking the adjacent layers of g-C3N4 covalently to realize a high surface area without excess mass loss in a one-step process by introducing diethylene glycol as a precursor that produces-(CH2)2-O-(CH2)2-linkers in-situ. Their presence increases interlayer spacing and introduces surface curvatures, discouraging the stacking of a larger number of layers to produce nanosheets with-3 times higher surface area. Interestingly, unlike other layered materials, the linkers also provide extraordinary mechanical stability against exfoliating forces. In addition, the process instills sub-bandgap states and a considerable visible light response at 500 nm to slow down the picosecond exciton recombination dynamics, resulting in-5 times enhancement in H2 generation efficiency from photocatalytic water-splitting over the bulk sample.
Keywords: Layer-linkers; Sustainable synthesis; Transient absorption spectroscopy; water-splitting